Answer:
g(4) = 7 and f(g(4)) = 43
Step-by-step explanation:
First find g:
g(x) = 3x-5
g(x) = 3(4) - 5
g(x) = 12 - 5
g(x) = 7
Plug in:
f(g(4))
f(7)
Now, find f:
7^2 - 7 + 1
49 - 7 + 1
42 + 1
f(x) = 43
Answer:
C
Step-by-step explanation:
First, get the radius, 2.2*3.14 is 6.908. Then, multiply by 18, 6.908*18 is 124.344.
Answer:
x<-3 or x>-1
Step by step explanation:
Start with -5x>15. To get x by itself, we have to divide each side by -5. When we do that we get x<-3. (Don't forget to flip the sign when dealing with negative · and ÷.) Now answer the second equation. x-5>-6 To get x by itself, add 5 to both sides to get x>-1. Now we have x<3 or x>-1.
Recall to always convert the mixed fractions to "improper" fractions first,